Infrequent development of resistance in genotype 1-6 hepatitis C virus-infected subjects treated with sofosbuvir in phase 2 and 3 clinical trials - Svarovskaia, Evguenia S; Dvory-Sobol, Hadas; Parkin, Neil; Hebner, Christy; Gontcharova, Viktoria; Martin, Ross; Ouyang, Wen; Han, Bin; Xu, Simin; Ku, Karin; Chiu, Sophia; Gane, Edward; et al. (Clinical infectious diseases, 2014)
Sofosbuvir is a chain-terminating nucleotide analogue inhibitor of the hepatitis C virus (HCV) NS5B RNA polymerase that is efficacious in subjects with HCV genotype 1-6 infection. Sofosbuvir resistance is primarily conferred by the S282T substitution in NS5B. NS5B sequencing and susceptibility testing of HCV from subjects infected with genotypes 1-6 who participated in phase 2 and 3 sofosbuvir clinical trials was performed. No NS5B variants present at baseline among 1645 sofosbuvir-treated subjects were associated with treatment failure; sofosbuvir susceptibility was within 2-fold of reference. Among 282 subjects who did not achieve sustained virologic response, no novel sofosbuvir resistance-associated variants were identified, and the NS5B changes observed did not confer significant reductions in sofosbuvir susceptibility. In 1 subject with S282T observed at relapse 4 weeks after sofosbuvir monotherapy, the resistant variant (13.5-fold reduced sofosbuvir susceptibility, replication capacity <2% of control) became undetectable by deep sequencing 12 weeks after treatment. L159F and V321A were identified as treatment-emergent variants but did not confer resistance to sofosbuvir in the replicon system. These data demonstrate a uniform susceptibility of subject-derived HCV to sofosbuvir, and also show that selection of sofosbuvir-resistant HCV is exceedingly rare and is associated with a significant reduction in viral fitness.